Ceremony as the Form of the Symbolic Communication of Prague Nuncio Antonio Caetani (1607–1611) (Theatrum historiae, 2015)
The diplomatic reports of papal nuncio Antonio Caetani, who worked at the imperial court in Prague in the years 1608–1609, record a few examples relating to a ceremony as a specific form of symbolic communication. Besides ceremonial meetings (incontro) and maintaining a certain sequence in the hierarchy of other diplomats, there are several events reflecting conflict situations in ceremonial practices.
Keywords: nuncio; Antonio Caetani; Imperial court; ceremonial practice; symbolic communication